AB1241 EVALUATION OF A PATIENT COMPLETED DISEASE FLARE QUESTIONNAIRE IN PSORIATIC DISEASE. (2nd June 2020) - Helliwell, P.; Tillett, W.; Waxman, R.; Coates, L. C.; Fitzgerald, O.; Packham, J.; Mchugh, N.
Abstract : Background: Psoriatic Disease (PsD) is a chronic inflammatory disease of the skin, nails, joints, and entheses. A number of composite disease activity measures have been developed though there is yet consensus as to which to use in the clinic and in clinical trials. A patient completed disease flare questionnaire, covering multiple domains of disease impact, has been developed but has yet to be fully validated. Objectives: To validate the FLARE questionnaire in PsD. Methods: The 10 question FLARE instrument 1 was administered to 141 patients in an observational study of treatment change in PsD over 6 months follow up. Disease activity was measured by the PASDAS and the gold standard of flare was based on patient opinion. ROC curve was constructed to examine the optimum cut-off for disease flare. Agreement between the FLARE instrument and patient opinion was assessed by Cohen's kappa. Test-retest was assessed in 28 patients with stable disease who underwent repeat assessment within 2 weeks and evaluated by intra-class correlation coefficient (ICC). Results: The FLARE questionnaire was administered at 367 patient encounters. ROC analysis indicated that the optimum cut-off for a flare of disease was 4 (sensitivity 82%, specificity 76%; area under curve 0.85: figure). Mean PASDAS scores were 2.7 and 6.3 for no-flare (4) and flare (≥4) respectively (p = < 0.0001). For those patients who were having a flare the frequency of response to each question is given in the table. Agreement between patient opinion and questionnaire was 0.57, and between patient opinion and physician (based on treatment escalation) 0.43. ICC for the questionnaire was 0.87 (95% CI 0.72 – 0.94). Conclusion: In PsD a flare represents escalation of symptoms and signs across multiple domains, as measured by the FLARE instrument; a score of 4 or more has external validity both in terms of composite disease activity and overall patient opinion of the state of their condition. References: [1]Moverley A, Waxman R, de Wit M, Parkinson A, Campbell W, Brooke M, et al J Rheum May 2016, 43 (5) 974-978 Acknowledgments: This report is independent research funded by the National Institute for Health Research, Programme Grants for Applied Research [Early detection to improve outcome in patients with undiagnosed PsA ('PROMPT'), RP-PG-1212-20007]. The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care Disclosure of Interests: Philip Helliwell: None declared, William Tillett Grant/research support from: AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant of: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, MSD, Pfizer Inc, UCB, Speakers bureau: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, Pfizer Inc, UCB, Robin Waxman: None declared, Laura C Coates: None declared, Oliver FitzGerald: None declared, Jon Packham: None declared, Neil McHugh: None declared